2022
DOI: 10.1096/fj.202101853rr
|View full text |Cite
|
Sign up to set email alerts
|

The genetic risk factors for pregnancy‐induced hypertension: Evidence from genetic polymorphisms

Abstract: Pregnancy‐induced hypertension (PIH) is a multifactorial and severe pregnancy complication including preeclampsia/eclampsia, gestational hypertension, chronic (pre‐existing) hypertension, and preeclampsia/eclampsia variants superimposed on chronic hypertension. PIH‐induced maternal mortality accounts for approximately 9% of all maternal deaths over the world. A large number of case‐control studies have established the importance of various genetic factors in the occurrence and development of PIH. In this narra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…The ACE I/D also increases the risk of hypertrophic cardiomyopathy [26], together with other variabilities of ACE [27]. Polymorphisms of the ACE and AT 1 R and AT 2 R genes seem to be associated with preeclampsia and pregnancyinduced hypertension [28]. Angiotensinogen is also a fairly conservative protein: several sequence features are maintained in 57 vertebrate species.…”
Section: Minor Variabilities Of the Human Ras Genesmentioning
confidence: 99%
“…The ACE I/D also increases the risk of hypertrophic cardiomyopathy [26], together with other variabilities of ACE [27]. Polymorphisms of the ACE and AT 1 R and AT 2 R genes seem to be associated with preeclampsia and pregnancyinduced hypertension [28]. Angiotensinogen is also a fairly conservative protein: several sequence features are maintained in 57 vertebrate species.…”
Section: Minor Variabilities Of the Human Ras Genesmentioning
confidence: 99%
“…In addition to previously mentioned variants, several scientists have also focused on genetic variations of renin‐angiotensin system (RAS), oxidative stress and other pathways that modulate blood pressure. Many of those are known to be associated with hypertensive disorders during pregnancy (mainly preeclampsia) (Wei et al., 2022). For example, variations in angiotensinogen ( AGT ), angiotensin receptor ( AGTR1 , AGTR2 ), and angiotensin‐converting enzyme ( ACE ) genes can modulate genetic expression and thus cause uncontrolled activation of RAS leading to hypertensive and other pregnancy complications (Ashour et al., 2022; Zotova et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal deaths caused by PIH account for about 9% of maternal deaths worldwide [10] . Animal experiments have found that RhoGAP involved in regulating blood pressure is positively correlated with functional cardiac development in mice.…”
Section: Introductionmentioning
confidence: 99%